Management of spontaneous pneumothorax: are British Thoracic Society guidelines being followed?. Issue 916 (1st February 2002) - Mendis, D; El-Shanawany, T; Mathur, A; Redington, A E
Abstract : In 1993, the British Thoracic Society (BTS) issued guidelines for the management of spontaneous pneumothorax. The aim of this study was to determine the level of adherence to and awareness of these guidelines at a London teaching hospital. A retrospective case note audit of 59 episodes of acute spontaneous pneumothorax was performed. In patients undergoing intervention, the initial procedure was simple aspiration in 32 (73%) and chest tube insertion in 12 (27%) cases, contrasting with the BTS recommendation that aspiration should be attempted first in all such patients. Simple aspiration was successful on 34% of occasions. Successful aspiration was associated with a significantly shorter hospital stay (median 3, range 1–11 days) than either failed aspiration (7, 3–66 days; p=0.003) or chest tube insertion without aspiration (9, 3–16 days; p=0.005). Other areas where practice differed from the BTS guidelines were clamping of chest tubes and use of a pursestring suture for wound closure. A follow up questionnaire survey suggested a lack of familiarity with the guidelines. These findings indicate that current management of spontaneous pneumothorax deviates from the BTS guidelines in a number of potentially important respects. Attention should be directed to improving awareness of and access to clinical guidelines.